Distinct mechanism of cervical cancer cell death caused by the investigational new drug SHetA2 - Rai, Rajani; Chandra, Vishal; Kennedy, Amy L.; Zuna, Rosemary E.; Benbrook, Doris Mangiaracina (Frontiers in Oncology, 2022)
Drug-targetable vulnerabilities of cancer cells include their dependence on heat shock proteins (HSPs) to support elevated mitochondrial metabolism and counteract cell death factors. The investigational new drug SHetA2 targets these vulnerabilities in ovarian and endometrial cancer cells by disrupting complexes of the mortalin HSP with its client proteins (mitochondrial support proteins, metabolic enzymes, p53) leading to mitochondrial leakage of cytochrome c and apoptosis-inducing factor (AIF), and caspase-dependent apoptosis. Our objective was to evaluate the roles of mitochondrial damage and another SHetA2-target HSP protein, cytoplasmic heat shock cognate 70 (hsc70), in the mechanism of SHetA2 killing of cervical cancer cells. Cervical cancer cells responded to SHetA2 with excessive mitophagy that did not deter AIF leakage into the cytoplasm. Then, hsc70 was unable to prevent cytoplasmic AIF nuclear translocation and promotion of DNA damage and cell death, because SHetA2 disrupted hsc70/AIF complexes. The Cancer Genome Atlas analysis found that overexpression of hsc70, but not mortalin, was associated with worse cervical cancer patient survival. Use of specific inhibitors documented that AIF and mitophagy, but not caspases, contributed to the mechanism of SHetA2-induced cell death in cervical cancer cells. As validation, excessive mitophagy and lack of caspase activation were observed in SHetA2-inhibited xenograft tumors.